Artificial Intelligence in Stroke – A Review (Journal of Pharmaceutical Negative Results, 2022)
Artificial intelligence is a computer science discipline that can analyse complex medical information. Almost every field of medicine has looked at the capabilities of artificial intelligence systems. Although artificial neural network were the most widely employed logical tool, other artificial intelligent approaches such as transformational computation and hybrid intelligent systems were also applied in a variety of clinical settings. Stroke is a cerebrovascular condition distinguished by the sudden onset of symptoms and scientific findings. Stroke is a main reason of death and morbidity in the world. It can be either ischemic or haemorrhagic, with the former caused by an in-place thrombus or a far-off embolus. The influence of gender on acute ischemic stroke presentation, severity, aetiology, and outcome is becoming more widely recognised. Seizures, conversion illness, migraine headache, and are the most common state that can copy a stroke.